2020
DOI: 10.3102/0002831220944908
|View full text |Cite
|
Sign up to set email alerts
|

Can Center-Based Care Reduce Summer Slowdown Prior to Kindergarten? Exploring Variation by Family Income, Race/Ethnicity, and Dual Language Learner Status

Abstract: This study examines growth in language and math skills during the summer before kindergarten; considers variation by family income, race/ethnicity, and dual language learner status; and tests whether summer center-based care sustains preschool gains. Growth in skills slowed during summer for all children, but the patterns varied by domain and group. Non-White and dual language learner students showed the largest drop-off in language skills during summer. Lower-income students demonstrated slower summer growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 75 publications
4
14
0
Order By: Relevance
“…These results align with prior studies focusing on later grades that have shown that schools mostly serve a compensatory function and are associated with lower levels of inequality than might have been otherwise expected in the absence of schooling (Condron, Downey, and Kuhfeld 2021;Downey 2020;Downey et al 2004;McCormick et al 2021). Whereas the bulk of similar prior studies have focused on kindergarten or later, we add to this conversation by documenting trends in inequality for prekindergarten and kindergarten in both academic and social/behavioral domains.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results align with prior studies focusing on later grades that have shown that schools mostly serve a compensatory function and are associated with lower levels of inequality than might have been otherwise expected in the absence of schooling (Condron, Downey, and Kuhfeld 2021;Downey 2020;Downey et al 2004;McCormick et al 2021). Whereas the bulk of similar prior studies have focused on kindergarten or later, we add to this conversation by documenting trends in inequality for prekindergarten and kindergarten in both academic and social/behavioral domains.…”
Section: Discussionsupporting
confidence: 90%
“…Our results also align with prior findings that suggest that schools' compensatory functions may be more related to language skills than to math skills (Condron et al 2021), although more research is needed to fully disentangle these patterns. These results are also consistent with prior work using the BPS data (McCormick et al 2021), which we build on by including nonacademic outcomes and outcomes that are disaggregated by race. Finally, assessments used in this study may include bias that shape our evaluation of the development of inequality, particularly for those that are teacher reported.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The studies (Table 1) offered summer reading programs to children at risk or at some risk of reading difficulties (Beach et al, 2018;Christodoulou et al 2017;Rafferty, 2012;Siddiqui et al, 2014;Zeng et al, 2016;Zvoch & Stevens, 2013) and behavioral problems (Hart et al, 2016;Rafferty, 2012;Zeng et al, 2016) or to low-income children (Beach et al, 2018;Gettinger & Stoiber, 2018;Hart et al, 2016;McCormick et al, 2021;Nicholson & Tiru, 2019;Pears et al, 2014;Siddiqui et al, 2014;Sinatra & Eschenauer, 2012;Xu & de Arment, 2017;Zvoch & Robertson, 2017). The programs ranged from 2 weeks to 8 weeks over a period of several years (i.e., longitudinal studies; Kraft & Monti-Nussbaum, 2017) or just for one summer and were administered to children in different grades (Christodoulou et al 2017;Gettinger & Stoiber, 2018;Nicholson & Tiru, 2019;Rafferty, 2012;Siddiqui et al, 2014;Sinatra & Eschenauer, 2012;White et al, 2014;Zeng et al, 2016;Zvoch & Stevens, 2013), or were used to prepare for the coming grade (Beach et al, 2018;Hart et al, 2016;McCormick et al, 2021;Pears et al, 2014;Zvoch & Robertson, 2017;Xu & de Arment, 2017). Thus, we have structured the narrative description of these studies according to their experimental design.…”
Section: Overview Of the Studiesmentioning
confidence: 99%
“…More recently, McCormick et al (2021) examined the extent to which the attendance at a drop-in center (linked to a state school or a community-based organization) could reduce summer loss before kindergarten entry as a function of socioeconomic status, race/ethnicity, and dual-language learner status over a two-year period. To do this, researchers examined the trajectories of reading and math skills of 323 children over the summer as a function of environmental and individual factors.…”
Section: Short-term Effect Of the Reading Program Involving Cross-sec...mentioning
confidence: 99%